Research on Security Connotation and Response Strategies for Big Data - Kun Hu; Di Liu; Minghui Liu (Dianxin kexue)
Big data is easy to understand which has many potential application requirements and foreseeable enormous economic benefits.With the development of mobile internet，cloud computing and M2M，big data become a new focus in the information technology field.But，it brings some challenges and problems，such as data security and privacy protection.The security requirements of big data in various fields were reviewed，and the security features and problems in big data environment were analyzed.Then the security connotation of big data was summarized and some response strategies were proposed.